Smart Circular Farming 4.0: IoT-and Solar Cell-Based Integration of Maggot Farming, Laying Hens, Biofloc Aquaculture, and Hydroponics for Village Food Security - Mastur, Mastur; Nugroho, Catur; Praharto, YB; Artati, Nuning; Winati, Famila Dwi; Qisthani, Nabila Noor; Arifin, Miftahol (Sarana Ilmu Indonesia (salnesia), 2025)
Located in a hilly area of Banyumas with high stunting and poverty rates, Windujaya Village faces significant geographical and infrastructural challenges. This community service program implements an integrated farming system based on Appropriate Technology (TTG) and a closed-loop production model. Key innovations include maggot cultivation, biofloc catfish farming, hydroponics, and an IoT-integrated smart chicken coop powered by solar energy. Through training and mentoring, the program successfully improved residents' skills, reduced feed and energy costs, and diversified income sources. The integration of IoT and sustainable farming models proved effective in enhancing food security and fostering adaptive community empowerment in marginalized areas.